The PENGARUH BRAND IMAGE, PERSEPSI HARGA, DAN ELECTRONIC WORD OF MOUTH KEPADA KEPUTUSAN PEMBELIAN PRODUK MAD FOR MAKEUP DI BANDUNG - Putry Hendriyani; Marheni Eka Saputri (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
Nowadays, interest in makeup products is on the rise. Local makeup products are also growing and innovating. One of the local makeup brands is Mad For Makeup. The purpose of this study was to analyze how purchasing decisions on Mad For Makeup products in Bandung are influenced by brand image, price perception, and e-word of mouth. Using a quantitative approach with descriptive and causal analysis. The sample was taken nonprobabilistically, with purposive sampling. The analysis in this study used descriptive and multiple linear regression. SPSS version 25 is used in processing data. The results showed that the brand image variable (X1), price perception (X2), and electronic word of mouth (X3) had significant partial and simultaneous implications for the decision to purchase Mad For Makeup products in Bandung. It is recommended that Mad For Makeup ensure that its brand is unique, make products that match the price offered with the benefits provided by the product, increase the membership of the "Rebels" community, and explain through its social media content the functions of the products offered.